2016
DOI: 10.1037/hea0000350
|View full text |Cite
|
Sign up to set email alerts
|

Smokers exhibit biased neural processing of smoking and affective images.

Abstract: Objective There has been growing interest in the role that implicit processing of drug cues can play in motivating drug use behavior. However, the extent to which drug cue processing biases relate to the processing biases exhibited to other types of evocative stimuli is largely unknown. The goal of the present study was to determine how the implicit cognitive processing of smoking cues relates to the processing of affective cues using a novel paradigm. Methods Smokers (n = 50) and non-smokers (n = 38) comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 13 publications
1
19
1
Order By: Relevance
“…Preclinical studies showed that the representation of value in the brain's valuation system adapts to the range of values available at any given time (Padoa‐Schioppa, ). Hence, including a wide array of emotional categories is necessary to accurately assess the incentive salience attributed to cues predicting rewards (Oliver et al, ; Versace, Engelmann, et al, ; Versace & Schembre, ). The large LPP difference that we observed between the predictive and the nonpredictive cues in this experiment suggests that researchers interested in understanding the role of cues as triggers of compulsive eating should consider how the availability of rewards during the experiment and the presence of other emotionally arousing stimuli might impact participants' neurobehavioral responses to the cues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies showed that the representation of value in the brain's valuation system adapts to the range of values available at any given time (Padoa‐Schioppa, ). Hence, including a wide array of emotional categories is necessary to accurately assess the incentive salience attributed to cues predicting rewards (Oliver et al, ; Versace, Engelmann, et al, ; Versace & Schembre, ). The large LPP difference that we observed between the predictive and the nonpredictive cues in this experiment suggests that researchers interested in understanding the role of cues as triggers of compulsive eating should consider how the availability of rewards during the experiment and the presence of other emotionally arousing stimuli might impact participants' neurobehavioral responses to the cues.…”
Section: Discussionmentioning
confidence: 99%
“…The second requisite to test our hypothesis is to classify individuals based on their tendency to attribute incentive salience to cues predicting food rewards. A classification based only on the differences between LPPs evoked by food‐related cues and neutral stimuli would not be appropriate because the responses evoked by nonfood‐related emotional stimuli must be taken into account to appropriately scale and interpret the cue‐minus‐neutral LPP difference (Oliver, Jentink, Drobes, & Evans, ; Versace, Engelmann, et al, ; Versace & Schembre, ). To avoid this pitfall, we proposed cluster analysis as a data‐driven classification approach capable of taking into account the LPP responses evoked by more than two contents.…”
Section: Introductionmentioning
confidence: 99%
“…While self-report offers an important window into the individual’s subjective experience, it does not provide information about the neuropsychological underpinnings of these experiences, therefore depriving researchers of information that can be used to develop new relapse prevention treatments 11 . Furthermore, if just cigarette-related and neutral stimuli are included in cue-reactivity experiments, researchers cannot draw strong conclusion about the meaning or the strength of the responses evoked by cigarette-related stimuli 11,12 . By including other motivationally relevant stimuli, varying both valence and arousal, researchers can determine the strength of the responses evoked by cigarette-related cues in relation to other non-drug-related motivationally relevant stimuli and better test the hypothesis that cigarette-related cues “hijack human brain motivational systems and promote drug seeking over alternative behaviors” 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Identifying emotions’ neural correlates has high clinical relevance because most psychological disorders are characterized by altered affective processes (American Psychiatric Association, 2013; Dunning et al, 2011; Moeller et al, 2014; Oliver, Jentink, Drobes, & Evans, 2016; Simmons et al, 2008; Wirkner et al, 2017; X. Zhang et al, 2014), and associating neural responses to specific symptoms and behaviors is likely to inform and foster the development of new evidence-based treatments (Dunning et al, 2011; Robbins, Gillan, Smith, de Wit, & Ersche, 2012; Wirkner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%